Sustainable Desalinator - An EPS@ISEP 2016 Project - Augustyns, Lies (2018)
The European Project Semester (EPS) is a one semester capstone project/internship framework offered by the EPS providers to engineering, product design and business undergraduates. While a student-centred project-based learning offer, EPS proposes a unique multidisciplinary and multicultural teamwork set up to promote soft, technical and scientific competencies. In the spring of 2016, the EPS at the Instituto Superior de Engenharia do Porto (ISEP) welcomed a team of engineering students who chose to develop a sustainable water desalinator, the working principle relying on solar energy and natural temperature differences to convert saline water into fresh water. This paper describes the team's journey, including the motivation, the solution design process, considering the technical & scientific state of the art as well as the potential impact in terms of ethics, sustainability and marketing, and the development and testing of the prototype. The results obtained validate the purpose of the developed system since a significant reduction of the salt water conductivity, to values of the same order of magnitude of tap water, were observed. Although improvements can be made, the desalinator prototype produced 70 ml/d of distilled water in late spring and 7 ml/d in midwinter atmospheric conditions.